2016
DOI: 10.1186/s12905-016-0294-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of intimate partner violence during pregnancy among married women in Abay Chomen district, Western Ethiopia: a community based cross sectional study

Abstract: Background Intimate partner violence during pregnancy is the most common form of violence that harms the health of women and the fetus but practiced commonly in developing countries. There is scarcity of information regarding intimate partner violence during pregnancy in Ethiopia. Thus, this study aimed to assess the prevalence and associated factors of intimate partner violence during recent pregnancy in Abay Chomen district, Western Ethiopia. Methods Community based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
79
15
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(124 citation statements)
references
References 15 publications
14
79
15
4
Order By: Relevance
“…However, a cross-sectional study among pregnant women in Tanzania gave the prevalence rates of 18% and 20% for sexual and physical violence, respectively 33. Also, a community-based cross-sectional study among 282 married pregnant women in Ethiopia reported even higher prevalence rates for all forms of IPV 34. The differences in results could be explained by true prevalence differences but also could be due to differences in social beliefs on what constitutes IPV, tools and scales that were used for data collection and analyses and sample size.…”
Section: Discussionmentioning
confidence: 99%
“…However, a cross-sectional study among pregnant women in Tanzania gave the prevalence rates of 18% and 20% for sexual and physical violence, respectively 33. Also, a community-based cross-sectional study among 282 married pregnant women in Ethiopia reported even higher prevalence rates for all forms of IPV 34. The differences in results could be explained by true prevalence differences but also could be due to differences in social beliefs on what constitutes IPV, tools and scales that were used for data collection and analyses and sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Data will be collected using structured and semi-structured questionnaire that is adapted from various literature [ 29 , 41 , 50 , 54 – 70 ]. The tool will be pretested and modified to suit with the local context.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, domestic VAW is significantly associated with various poor health outcomes (low birth weight, premature birth, malnutrition, suicide, homicide, mental illness, physical injuries, disability and non-communicable diseases) [ 1 , 6 , 7 , 18 , 20 , 24 29 ]. In addition, VAW has been associated with HIV and other sexual transmitted infections (STIs) acquisition, unintended pregnancy, induced abortion and other poor reproductive health conditions [ 1 , 5 , 7 , 10 , 14 , 19 21 , 23 , 27 , 30 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…4 Social support (having e Social support (having ev ver liv er lived with a partner' ed with a partner's family) s family): : Two studies reported a significant relationship between social support and gender-based violence. 24,26 Having lived with a partner's parents was shown to be less likely associated with GBV. P Parit arity and family siz y and family size e: : Two studies reported that parity and family size were significantly associated with GBV.…”
Section: Victim Factorsmentioning
confidence: 99%
“…This was reported by only one study. 26 Having e Having experienc xperienced abuse of mo ed abuse of mother ther: : Two studies reported that women who experienced abuse of mother in the past, were more likely to be abused. 11,19 PERPETRATOR FACTORS Two studies were carried out among men alone and predictors reported in these studies include sexual history, previous experience of abuse, educational status, substance use, gender-biased attitude, and having experienced abuse of mother.…”
Section: Victim Factorsmentioning
confidence: 99%